Fostering Sport Employees’ Passion and Enhancing Organizational Success in Intercultural Sporting Events - Young Do Kim; Chanwook Do; Paul Yuseung Doh (Journal of Applied Sports Management, 2024)
This study emphasizes the role of sport employees’ passion in intercultural sporting events, specifically within professional sport leagues in the United States. The proposed framework identifies key factors that shape employee passion and explore its impact on organizational success, highlighting how fostering passion enhances innovative work behavior, intercultural communication effectiveness, task performance, and psychological well-being. Additionally, this research highlights the importance of cultural intelligence and meaningful work within the conceptual framework. The study offers strategies for sports organizations to cultivate passion, thereby strengthening employees’ work behavior in intercultural sporting contexts.
Keywords: sport employees’ passion; intercultural sporting events; cultural intelligence; psychological well-being; meaningful work